Three additions to the phanerogamic flora of Mexico - Rzedowski, Jerzy; Calderon de Rzedowski, Graciela (Instituto de Ecología, A.C., 1995)
Geniostemon rotundifolius (Gentianaceae), from the state of Querétaro, Stachys turneri (Labiatae), from the state of Guanajuato, and Vernonia solorzanoana (Compositae, Vernonieae), from the state of Michoacán, are described as new species. The first taxon differs from all known species of Geniostemon in its suborbicular, petiolate and trinerved leaves as well as in its purplish-brown anthers. The second species presents a so far unknown combination of the following characters: wooly stems and leaves, purple corollas with tubes ca. 1 cm long and apically pubescent ovary. The third one is similar to Vernonia baadii (McVaugh) S. B. Jones, but can be distinguished in being a much more pubescent plant, in its stramineous phyllaries and in the inflorescences with narrower leaves.